HGF Secreted by Activated Kupffer Cells Induces Apoptosis of Plasmodium-Infected Hepatocytes - Gonçalves, Lígia Antunes; Rodo, Joana; Rodrigues-Duarte, Lurdes; de Moraes, Luciana Vieira; Penha-Gonçalves, Carlos (Frontiers in Immunology, 2017)
Malaria liver stage infection is an obligatory parasite development step and represents a population bottleneck in Plasmodium infections, providing an advantageous target to block parasite cycle progression. Parasite development inside hepatocytes implies a gross cellular insult evoking innate host responses to counteract intra-hepatocytic infection. Using primary hepatocyte cultures, we investigated the role of Kupffer cell-derived hepatocyte growth factor (HGF) in malaria liver stage infection. We found that Kupffer cells from Plasmodium-infected livers produced high levels of HGF, which trigger apoptosis of infected hepatocytes through a mitochondrial-independent apoptosis pathway. HGF action in infected hepatocyte primary cultures results in a potent reduction of parasite yield by specifically sensitizing hepatocytes carrying established parasite exo-erythrocytic forms (EEFs) to undergo apoptosis. This apoptosis mechanism is distinct from cell death that is spontaneously induced in infected cultures and is governed by Fas signalling modulation through a mitochondrial-dependent apoptosis pathway. This work indicates that HGF and Fas signalling pathways are part of an orchestrated host apoptosis response that occurs during malaria liver stage infection, decreasing the success of infection of individual hepatocytes. Our results raise the hypothesis that paracrine signals derived from Kupffer cell activation are implicated in directing death of malaria-infected hepatocytes.